Exploring the Status of Teaching Listening and Speaking Skills after the Introduction of their Tests in Secondary Level Education - Md. Nahid Ferdous Bhuiyan; Md. Shamsul Huda (Crossings, 2020)
Among the four skills of a language, listening and speaking are often considered to be more frequently used skills in real life communication. Many studies show that English listening and speaking skills were less or rarely taught in the classroom mainly because these were not tested in public or internal exams in Bangladesh. But the National Curriculum (2012) also suggests testing these skills. The Ministry of Education (2015) consequently released a circular to administer these tests in the internal exams in secondary level education. This research intended to study the teaching of these two skills, the practice of tests of these two skills, and the challenges in administering the tests. It finds that the teaching practices of these two skills in the classroom have increased compared to those in the past but not at an optimal level. These tests are not given in the terminal examinations and administered only as continuous assessments. This study finds that 67% help learners develop their listening skills by using English in the class, 60% teach listening activities, and 53% teachers teach speaking skills. However, 30% schools still do not give their students these two tests. Practicing TEFL teachers identified some challenges in administering these tests. Their suggestions for solving these problems are also given.